PENGARUH KUALITAS PELAYANAN TERHADAP LOYALITAS MAHASISWA MELALUI KEPUASAN MAHASISWA DI STKIP PANCA SAKTI PONDOK GEDE - Hafifi Hafifi (Fakultas Ekonomi Universitas Borobudur, 2018)
Based on preliminary research, the declining amount of the new students each year and the rise of student drop-out for the past three years at STKIP Panca Sakti Pondok Gede are caused by the weakness of the service quality by the management. That’s why this research is done to find out “ How far is the influence of service quality towards the student loyalty through the student satisfaction”The research has resulted that first, the service quality significantly and directly influences the student satisfaction. H0, therefore, (the influence of the service quality towards the student satisfaction is not significant) is rejected and H1 (the influence of the service quality towards the student satisfaction) is excepted. Second, the student satisfaction significantly and directly influences the student loyalty. H0 (The influence of student satisfaction towards the student loyalty is not significant) is rejected, and H1 (the influence of students’ satisfaction toward the student loyalty is significant) is excepted. Third, the service quality significantly influences directly the students’ loyalty. H0 (The influence of the service quality towards the student loyalty is not significant) is rejected, and H1 (The influence of the service quality towards the students’ loyalty is significant) is excepted. And, finally, the influence of service quality indirectly through the student satisfaction towards the student loyalty is significant. H0 (The influence of the service quality towards the student loyalty indirectly through the student satisfaction is not significant) is rejected, and H1 (The influence of the service quality towards the student loyalty indirectly through the student satisfaction is significant) is excepted. Key words: Service Quality, Student Satisfaction, and Student Loyalty.